Unraveling brucellosis: advances in pathogenesis, diagnostic strategies, therapeutic innovations, and public health perspectives - Almuzaini, Abdulaziz M.; Elbehiry, Ayman (Frontiers in Medicine, 2025)
Brucellosis remains one of the most impactful zoonotic diseases worldwide, posing major socioeconomic and public health challenges, particularly in low- and middle-income countries. This review presents recent progress in understanding the pathogenesis of Brucella species, emphasizing the role of key adhesins—SP29, SP41, BigA, BigB, BamA, BmaB, BmaC, Bp26, BtaF, and BtaE—in host-pathogen interactions that drive adhesion, invasion, and immune evasion. We also critically assess current diagnostic approaches, including conventional culture techniques, serological assays, and emerging molecular platforms, which offer improved sensitivity and specificity. Current treatment regimens involve extended antibiotic combinations—typically doxycycline with rifampin or streptomycin—and may include surgical intervention in complicated cases. Additionally, the integration of nanotechnology-based drug delivery and traditional Chinese medicine offers promising adjunctive therapies. Although several animal vaccines exist, no approved vaccine is currently available for human use. Novel vaccine platforms, including live vectors, DNA subunits, and nanoparticle-based formulations, are under development. Finally, we address the disease's broad socioeconomic impact—ranging from livestock losses to healthcare burdens—and highlight ongoing challenges, such as diagnostic limitations, antimicrobial resistance, underreporting, and barriers to vaccine development. A One Health approach, alongside translational research and integrated surveillance, is vital to advancing prevention and control strategies for this neglected zoonosis.